Overcoming The Myth of Arabic Rigidity: Quantum Innovation And Hypermedia Inspiring the Spirit of Learning - Nurul Hanani; Afifah Mayaningsih (UIN Sunan Gunung Djati Bandung, 2024)
This study attempts to provide a conceptual map of Arabic language teaching using a methodological mapping approach. Arabic language has long been negatively perceived as difficult, boring, and complex, ultimately leading to severe rigidity and a loss of motivation. The aim of this research is to combine educational concepts using quantity and hypermedia, meaning methods and educational approaches aimed at dispelling the negative perceptions and reviving the motivation to learn Arabic. This research is conducted through a qualitative approach with the assumption of developmental research. Non-probabilistic sampling using purposive sampling (non-random) with observational data sampling techniques was employed in Pondok Pesantren Al-Amin Perinduan Sumenep and Nurul Jadid Probolingo, East Java. The results of this study indicate that the application of the quantum and hypermedia methods can reduce students' stiffness in learning the Arabic language. This research contributes to the analysis and appropriate steps in other subjects as well.